Integrated condition assessment for Navy system of systems. (1st January 2012) - Hester, Patrick T.; Adams, Kevin MacG.; Kern, David J.
Although the US Navy has made great strides in integrating technology to monitor and assess the condition of sub-systems, little is understood about how to fuse this data in order to construct a higher level awareness of the ship's overall readiness or current state. Drawing upon systems theory and systems-based approaches, we identify principles of hierarchy, control, suboptimisation, and satisficing as critical propositions for fusing integrated condition data and propose the viable system model as a hierarchical construct for managing the complexity of fusing integrated data into higher level awareness. This research resulted in the development of a system-level decision process that represents the underlying process of maintaining awareness of system level condition. We feel that further study is needed to fully realise the potential of using the a system-level decision process in integrating data for condition-based assessment and suggest avenues of research in calculating system reliability in managing both aleatory and epistemic uncertainty resident in the system.